A Mycorrhizal Bacteria Strain Isolated From Polyporus umbellatus Exhibits Broad-Spectrum Antifungal Activity - Han, Pengjie; Liu, Tianrui; Zheng, Yuan; Song, Ruiqi; Nan, Tiegui; Yang, Xiaolong; Huang, Luqi; Yuan, Yuan (Frontiers in Plant Science, 2022)
The microbes in the rhizosphere (or mycorrhizosphere) could promote plant growth, however, it is unclear whether mycorrhizosphere microbes could fight multiple fungal pathogens. In this study, twenty-one bacterial strains distributed in 6 genera, including 5 Pseudomonas strains, were isolated from mycorrhizal samples of Polyporus umbellatus that rely on other fungi during their life cycles. Further screening and pot experiments showed that the Pseudomonas strain ZL8 not only inhibited the growth of phytopathogenic fungi, but also promoted the growth of Salvia miltiorrhiza through inhibiting its wilting. In addition, strain ZL8 was found to have the ability to dissolve phosphate, produce IAA and siderophore. Nineteen compounds were identified from the fermentation broth of strain ZL8, of which 2,4-diacetylphloroglucinol (DAPG) had a significant inhibitory effect on phytopathogenic fungi with a minimum inhibitory concentration of 3.12–25 μg/mL. Molecular docking predicted that DAPG could bind to myosin I at two unique sites, which may be responsible to the inhibition of fungal growth. The evaluation results showed that strain ZL8 can be used to develop a dual-purpose biocontrol agents and biofertilizer. These results also provide new insights into the discovery and utilization of new resources for biocontrol agents and biolfertilizers.